2019
DOI: 10.1016/j.enpol.2018.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Interactions in Swiss households’ energy demand: A holistic approach

Abstract: This article explores the interactions between direct and embodied energy requirements of households in Switzerland in order to assess the net impacts of standard energy policies focusing exclusively on direct energy use. For this purpose, we estimate direct and embodied energy demand of Swiss households by combining consumption data of a national expenditure survey with corresponding data on energy intensity mainly from life-cycle analysis. We find strong evidence of complementarity between direct and grey en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 93 publications
1
4
0
Order By: Relevance
“…The coefficient associated to Y tends to increase from 0.32 to 0.43 with the quantile. These elasticity values are quite similar to those observed in the study by Tilov et al (2019), who also found elasticity values increasing with the quantile. Thus, the response of the residential electricity use to income, tends to increase as the quantile grows, that is, as the electricity consumption grows in per capita terms.…”
Section: Quantile Regression Estimate Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The coefficient associated to Y tends to increase from 0.32 to 0.43 with the quantile. These elasticity values are quite similar to those observed in the study by Tilov et al (2019), who also found elasticity values increasing with the quantile. Thus, the response of the residential electricity use to income, tends to increase as the quantile grows, that is, as the electricity consumption grows in per capita terms.…”
Section: Quantile Regression Estimate Results and Discussionsupporting
confidence: 90%
“…Therefore, this study enlarges on previous literature related to temperature effects on residential energy consumption. To our knowledge, only the study by Tilov et al (2019), analyzes the CDD and HDD effects on household energy demand, by differentiating by quantiles, but uses a linear specification. On the contrary, in this study, a non-linear CDD and HDD effect is considered, allowing changing by energy quantiles.…”
Section: Electricity Consumption and Temperature Effectsmentioning
confidence: 99%
“…fig 3b). Tilov et al (2019) estimate separately income-elasticity for direct energy (at 0.11) and embodied energy (at 0.47). The latter thus provides an upper bound on the incomeelasticity of total (direct and embodied) energy requirements.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Salari and Javid ( 2017 ), by analyzing a rich US dataset, find that among other determinants, demographical features and building characteristics are the two most important determinants of household energy expenditure, similar to some of the findings by Kavousian et al ( 2015 ) that studies Irish household data. Further evidence of influences on energy demand from household characteristics have been observed in a range of other countries (Couture et al 2012 in France; Ajayi 2018 in Nigeria; Jayaraj et al 2011 in India; Tilov et al 2019 in Switzerland; and Bissiri et al 2019 who compares German and British households). Other micro studies that focus on more classical economic determinants of energy demand have found a negative relationship with energy price (Filippini 2011 ) and a positive relationship with income (as well as education; Hansen 2016 ).…”
Section: Literaturementioning
confidence: 85%